Biliary and systemic bacteriology in acute septic cholangitis - Estefan, Alberto; Cireluello, Roberto; Pedreira, Walter; Montano, Daniel; Fernández, Gonzalo; Bagnulo, Homero (Cirugía del Uruguay, 1992)
The authors make a prospective study on 31 cases of «genuin» acute septic cholangitis in arder to establish: 1. frequence of positive bili and hemocultures far aerobic and anaerobic germs. 2. bacteria present in bili and hemocultures 3. rational antibioticotherapy «according to the focur» 4. if there is a relationship between mortality and the presence of one germ or an association of them, the existence of positive hemocultures, the number of majar physiological systems affected andlor etiology.